Research of High-Precision Control Method for Rotary Flying Shear - Jun Song (Forest Chemicals Review, 2022)
In the high-speed operation, we should not only accurately cut the cut point on the material according to the production requirements to complete the cut, and but also ensure the relative speed matching between the cut blade and the material in the cut process to protect the cut blade. As a result, there is extremely high requirement for the control accuracy of the rotary flying shear. In this paper, through the physical analysis of the cut process, the motion law of the rotary flying shear and the motion track of the cut blade are obtained, and a complete control method of the rotary flying shear is put forward by combining the control theory analysis with the motion track of the cut blade. This method fully meets the control requirements when the cut blades are in different positions in the cut process, and can significantly improve the speed and position control accuracy of flying shears, providing a good foundation for the optimization of control parameters of rotary flying shears with different structures.